Pengaruh Pendekatan Berpikir Kausalitik Scaffolding Tipe 2a Modifikasi Berbantuan LKS Terhadap Kemampuan Pemecahan Masalah Optik Geometri Dan Kreativitas Siswa Kelas XI SMAN 1 Mataram - Fuad Tamami; Joni Rokhmat; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2017)
Scaffolding thinking approach is a specific method to facilitate students in determining cause and effect of phenomenon and identifying each cause happen in which assist are given. This research aims to investigate the effect of worksheet assisted causalitic thinking type 2a scaffolding modified approach toward student`s problem solving ability (PSA) and creativity among second grade student at SMAN 1 Mataram. This research is a quasi experimental with research design is pretest posttest control group. The population in this research are all students of XI Sains with sampling method is purposive sampling. Problem solving ablility measured using PSA test. Meanwhile, creativity measured using verbal and figural test. Problem solving ability and creativity analyzed using t-test separated varians with 5% significant level. The result of hypothesis test for problem solving ability is obtained tcount > ttable and for creativity obtained tcount < ttable. Based on the analysis result, it can be concluded that: (1) there is an effect of worksheet assisted causalitic thinking type 2a scaffolding modified approach toward the student`s problem solving ability in optical geometry. (2) there is no effect of worksheet assisted causalitic thinking type 2a scaffolding modified approach toward student`s creativity.